THE CORRELATION OF STUDENTS' ANXIETY AND READING COMPREHENSION (CASE STUDY) AT POLITEKNIK UNGGUL LP3M MEDAN (3rd Semester Students) - Handayani, Cici; Yani, Selfitrida A (Universitas Dharmawangsa, 2025)
This study investigates the correlation between students’ reading anxiety and their reading comprehension performance in higher education. Reading comprehension is a critical academic skill, yet many students struggle due to emotional factors such as anxiety, which can impair focus, memory, and cognitive processing. A total of 50 undergraduate students participated in this correlational study. Reading anxiety was measured using the Foreign Language Reading Anxiety Scale (FLRAS), while reading comprehension was assessed through a standardized test consisting of multiple-choice and short-answer questions. Data were analyzed using descriptive statistics, Pearson correlation, and simple linear regression. The results indicated a strong negative correlation (r = -0.62, p < 0.01) between reading anxiety and comprehension scores, suggesting that higher anxiety levels significantly reduce students’ reading performance. Regression analysis revealed that reading anxiety accounted for 38% of the variance in reading comprehension scores. The findings highlight the need for targeted interventions, such as relaxation techniques, cognitive-behavioral strategies, and structured reading activities, to reduce anxiety and enhance comprehension skills. This study provides valuable insights for educators and researchers in designing strategies to support students’ emotional well-being and academic success.